Behaviour of Al2O3-oxide insulated and non-insulated superconducting MgB2 coils cooled by water ice. (1st September 2022) - Kováč, P; Búran, M; Kopera, L
Abstract: Wind-and-react coils made using non-insulated and/or Al2 O3 oxide-insulated internal magnesium diffusion-processed MgB2 wires were energized at low temperatures with the help of sub-cooled water ice. The results demonstrate thermally stable winding behaviour and current densities (>10 4 A cm −2 for T < 30.5–33 K) of oxide-insulated and metal-insulated MgB2 coils. The expansion caused by the water-to-ice transformation does not degrade the windings or the Al2 O3 insulation. The thermometers and Hall probe are also undamaged over the full temperature range of 27–297 K. Consequently, water ice provides a cheap and safe prospective cooling mode for various superconducting windings and future He-free systems.